The Potential Role of Plant Polysaccharides in Treatment of Ulcerative Colitis - Yilizilan Dilixiati; Adila Aipire; Ming Song; Dilaram Nijat; Abudukahaer Wubuli; Qi Cao; Jinyao Li (MDPI AG, 2024)
Ulcerative colitis (UC) results in inflammation and ulceration of the colon and the rectum's inner lining. The application of herbal therapy in UC is increasing worldwide. As natural macromolecular compounds, polysaccharides have a significant role in the treatment of UC due to advantages of better biodegradation, good biocompatibility, immunomodulatory activity, and low reactogenicity. Therefore, polysaccharide drug formulation is becoming a potential candidate for UC treatment. In this review, we summarize the etiology and pathogenesis of UC and the therapeutic effects of polysaccharides on UC, such as regulating the expression of cytokines and tight junction proteins and modulating the balance of immune cells and intestinal microbiota. Polysaccharides can also serve as drug delivery carriers to enhance drug targeting and reduce side effects. This review provides a theoretical basis for applying natural plant polysaccharides in the prevention and treatment of UC.